Viral etiologies of influenza‐like illness and severe acute respiratory infections in Thailand. Issue 4 (8th May 2018) - Chittaganpitch, Malinee; Waicharoen, Sunthareeya; Yingyong, Thitipong; Praphasiri, Prabda; Sangkitporn, Somchai; Olsen, Sonja J.; Lindblade, Kim A.
Abstract : Background: Information on the burden, characteristics and seasonality of non‐influenza respiratory viruses is limited in tropical countries. Objectives: Describe the epidemiology of selected non‐influenza respiratory viruses in Thailand between June 2010 and May 2014 using a sentinel surveillance platform established for influenza. Methods: Patients with influenza‐like illness (ILI; history of fever or documented temperature ≥38°C, cough, not requiring hospitalization) or severe acute respiratory infection (SARI; history of fever or documented temperature ≥38°C, cough, onset <10 days, requiring hospitalization) were enrolled from 10 sites. Throat swabs were tested for influenza viruses, respiratory syncytial virus (RSV), metapneumovirus (MPV), parainfluenza viruses (PIV) 1‐3, and adenoviruses by polymerase chain reaction (PCR) or real‐time reverse transcriptase‐PCR. Results: We screened 15 369 persons with acute respiratory infections and enrolled 8106 cases of ILI (5069 cases <15 years old) and 1754 cases of SARI (1404 cases <15 years old). Among ILI cases <15 years old, influenza viruses (1173, 23%), RSV (447, 9%), and adenoviruses (430, 8%) were the most frequently identified respiratory viruses tested, while for SARI cases <15 years old, RSV (196, 14%) influenza (157, 11%) and adenoviruses (90, 6%) were the most common. The RSV season significantly overlapped the larger influenza season from July to November in Thailand. Conclusions: The global expansion of influenza sentinel surveillance provides an opportunity to gather information on the characteristics of cases positive for non‐influenza respiratory viruses, particularly seasonality, although adjustments to case definitions may be required.